Payenia Quaternary flood basalts (southern Mendoza, Argentina): Geophysical constraints on their volume - Spagnuolo, Mauro Gabriel (2016)
The Quaternary volcanic province of Payenia is located in southern Mendoza and northern Neuquén provinces of Argentina and is characterized by a dominant basaltic composition. The volcanic province covers an area larger than 40,000 km2 and its origin and evolution has been the center of several studies. In this study we analyzed gravity data together with more accurate volcanic volumes calculations in order to investigate the subsurface structure of the Payenia volcanic province. The volume of material was calculated using digital elevation models and geographic information system (GIS) techniques to estimate the volume of material erupted and then, with those values, make an estimation of the intrusive material that could be located within the crust. The results of the calculations were compared with different 2D-sections constructed to model the gravity data and compare with the observed satellite gravity. After evaluating different models which have been generated to match both: the observed gravity data and the subsurface material calculated, we discuss those that best fit with observation. The results clearly indicate that the lithosphere is attenuated below the region.